LOGISTICS ACTIVITIES AND THEIR IMPACT ON USER SATISFACTION AT PORT OF TANJUNG WANGI: Aktivitas Logistik dan Pengaruhnya Terhadap Kepuasan Pengguna Di Pelabuhan Tanjung Wangi - Saiful Rohman; Fandi Ahmad (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Ports serve as a crucial supply chain node coordinating integrated stevedoring activities and cargo distribution. The performance of both activities directly impacts service user satisfaction, yet empirical evidence at feeder ports like Tanjung Wangi Port remains limited. This explanatory quantitative study aims to analyze the influence of stevedoring (X1) and distribution (X2) on service user satisfaction (Y) at Tanjung Wangi Port. Data were gathered via 1–5 Likert scale questionnaires from 83 respondents selected through purposive sampling, comprising sea freight forwarders (EMKL), shipping agents, and cargo owners. Data analysis used multiple linear regression with SPSS software. The results indicate that stevedoring (X1) and distribution (X2) simultaneously exert a significant and substantial effect 67,4% on service user satisfaction (Y) (R2 = 0,674). Partially, the distribution (X2) (b = 0.512; t = 5.565) shows a more dominant influence than stevedoring activities (X1) (b = 0.456; t = 5.365). These findings imply that service user satisfaction (Y) at Tanjung Wangi Port is primarily determined by downstream distribution smoothness, including cargo release speed and streamlined administrative procedures. Practically, port management must prioritize simplifying distribution workflows to sustainably enhance user satisfaction.